Pembinaan dalam Upaya Meminimalisir Resiko Pengembalian Dana Pinjaman Modal Pada UMKM di Bank Wakaf Mikro Syariah Denanyar Jombang - Eny Latifah; Yusuf Yusuf; Nouvel Zabidi (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Bank Wakaf Mikro (BWM) Sumber Barokah Denanyar Jombang is one of ten Islamic MFIs in the early stages of the 'Community Empowerment through the Establishment of Islamic MFIs around Pesantren‛ Program facilitated by the Financial Services Authority (OJK) and the Small Business Incubation Center (Pinbuk) by providing loan funds for more productive community business groups. The purpose of this assistance is to provide guidance and direction on the knowledge and implementation of the efforts to be made by the Denanyar Jombang Sharia Micro Waqf Bank in minimizing the risk of capital loans given to MSMEs as business capital. There are three (3) stages in this assistance: Preparation, Implementation and evaluation. The results of the assistance show: (1) An increase in efforts to minimize the risk of capital loans, (2) A decrease in the number of defaults on the risk of returning loan capital (3) An increase in family values and religiosity for customers who make loans.